2021
DOI: 10.1177/13548166211034437
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness in the visitor economy: A systematic literature review

Abstract: Competitiveness is a well-discussed research topic in various disciplines and fields, amongst which competitiveness in the visitor economy is a prominent research stream. With rapid transformations in the visitor economy, destinations, regions, sectors and businesses have had to adapt – with varying degrees of success – to internal and external changes, significantly affecting their competitiveness. Existing studies are dominantly based on a few pioneering models and indicators and relatively few empirically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 95 publications
(152 reference statements)
0
13
0
Order By: Relevance
“…Still lacking in the existing literature, however, is an investigation of the impact of hotel-specific variables on the competitiveness of Airbnb listings, as well as a separate investigation of commercial and private Airbnb listings, whereby the former may ex-ante be characterized by a more efficient use of their inputs than the latter. This is the gap in the literature the present study tries to fill, which has also only very recently been confirmed as a research gap in a systematic literature review on the competitiveness of the visitor economy by Kim et al (2021).…”
Section: Related Literaturementioning
confidence: 71%
“…Still lacking in the existing literature, however, is an investigation of the impact of hotel-specific variables on the competitiveness of Airbnb listings, as well as a separate investigation of commercial and private Airbnb listings, whereby the former may ex-ante be characterized by a more efficient use of their inputs than the latter. This is the gap in the literature the present study tries to fill, which has also only very recently been confirmed as a research gap in a systematic literature review on the competitiveness of the visitor economy by Kim et al (2021).…”
Section: Related Literaturementioning
confidence: 71%
“…Other advantages include avoiding the use of additional software, since it also provides a set of tools for data visualization and ensures statistical correctness and completeness of results [62,63]. Bibliometrix is spreading in many domains of academic research such as economics [64], business and management [63,65,66], tourism and hospitality [67][68][69], open innovation [70], politics [71,72], and psychiatry [73]. Our work is conducted following a precise bibliometric workflow (reported in Figure 1): data collection, data analysis, and data visualization [59].…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected in 2018, through personal questionnaires with the head of the travel party at the main gateways of the country, including 15 airports and 12 land borders. 3 This research design is relevant as there is a prevalence of investigations of competitiveness at the destination/national level in the literature, despite the need for a broader understanding of competitiveness at different levels of a visitor economy (Kim et al, 2021). Likewise, the research is based on a destination located on a continent other than Europe, which is the focus of most studies on the topic (Cronjé and Du Plessis, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Second, there is an overemphasis on the national level approach and less knowledge about other levels of the visitor’s economy (e.g., regional or sectoral and micro level). Third, most studies are based on hidden cause-and-effect assumptions of different competitiveness factors (Abreu-Novais et al, 2016; Croes and Rivera, 2010; Cronjé and du Plessis, 2020; Kim et al, 2021; Tsai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation